Limited biomass recovery from gold mining in Amazonian forests. Issue 9 (28th June 2020) - Kalamandeen, Michelle; Gloor, Emanuel; Johnson, Isaac; Agard, Shenelle; Katow, Martin; Vanbrooke, Ashmore; Ashley, David; Batterman, Sarah A.; Ziv, Guy; Holder‐Collins, Kaslyn; Phillips, Oliver L.; Brondizio, Eduardo S.; et al.
Abstract: Gold mining has rapidly increased across the Amazon Basin in recent years, especially in the Guiana shield, where it is responsible for >90% of total deforestation. However, the ability of forests to recover from gold mining activities remains largely unquantified. Forest inventory plots were installed on recently abandoned mines in two major mining regions in Guyana, and re‐censused 18 months later, to provide the first ground‐based quantification of gold mining impacts on Amazon forest biomass recovery. We found that woody biomass recovery rates on abandoned mining pits and tailing ponds are among the lowest ever recorded for tropical forests, with close to no woody biomass recovery after 3–4 years. On the overburden sites (i.e. areas not mined but where excavated soil is deposited), however, above‐ground biomass recovery rates (0.4–5.4 Mg ha −1  year −1 ) were within the range of those recorded in other secondary forests across the Neotropics following abandonment of pastures and agricultural lands. Our results suggest that forest recovery is more strongly limited by severe mining‐induced depletion of soil nutrients, especially nitrogen, than by mercury contamination, due to slowing of growth in nutrient‐stripped soils. We estimate that the slow recovery rates in mining pits and ponds currently reduce carbon sequestration across Amazonian secondary forests by ~21, 000 t C/year, compared to the carbon that would have accumulated following more traditional land uses such as agriculture or pasture. Synthesis and applications . To achieve large‐scale restoration targets, Guyana and other Amazonian countries will be challenged to remediate previously mined lands. The recovery process is highly dependent on nitrogen availability rather than mercury contamination, affecting woody biomass regrowth. The significant recovery in overburden zones indicates that one potential active remediation strategy to promote biomass recovery may be to backfill mining pits and ponds with excavated soil. Abstract : To achieve large‐scale restoration targets, Guyana and other Amazonian countries will be challenged to remediate previously mined lands. The recovery process is highly dependent on nitrogen availability rather than mercury contamination, affecting woody biomass regrowth. The significant recovery in overburden zones indicates that one potential active remediation strategy to promote biomass recovery may be to backfill mining pits and ponds with excavated soil. Resumen: La minería de oro ha aumentado rápidamente en la cuenca del Amazonas en los últimos años, especialmente en el Escudo Guayanés, donde es responsable de >90% de la deforestación total. Sin embargo, la capacidad de los bosques para recuperarse de las actividades de extracción de oro sigue sin estar cuantificada. Se instalaron parcelas de inventario forestal en minas recientemente abandonadas, en dos regiones mineras importantes de Guyana, y se volvió a censar 18 meses después, para producir la primera cuantificación terrestre de los impactos de la extracción de oro en la recuperación de la biomasa del bosque amazónico. Descubrimos que las tasas de recuperación de biomasa leñosa, en pozos mineros abandonados y en estanques de relave, se encuentran entre las tasas más bajas registradas para bosques tropicales, con una recuperación de biomasa leñosa casi nula después de 3–4 años. Sin embargo, en los sitios de sobrecarga (es decir, áreas sin extracción, pero donde se deposita el suelo excavado), las tasas de recuperación de biomasa aérea (0.4–5.4 Mg ha −1  año −1 ) estuvieron dentro del rango de las tasas registradas en otros bosques secundarios en todo el Neotrópico tras el abandono de pastizales y tierras agrícolas. Nuestros resultados sugieren que la recuperación del bosque está limitada, con mayor fuerza, por el severo agotamiento de nutrientes del suelo, especialmente nitrógeno, que ha sido inducido por la minería, que el causado por la contaminación por mercurio, debido a la desaceleración del crecimiento en suelos despojados de nutrientes. Estimamos que las bajas tasas de recuperación en los pozos y estanques mineros reducen, en este momento, el secuestro de carbono en los bosques secundarios amazónicos en ~21, 000 t C/año, en comparación con el carbono que se habría acumulado siguiendo usos más tradicionales agrícolas o de pastizales. Síntesis y aplicaciones . Para lograr objetivos de restauración a gran escala, Guyana y otros países amazónicos tendrán el desafío de remediar tierras anteriormente mineras. El proceso de recuperación depende en gran medida de la disponibilidad de nitrógeno, más que en la contaminación por mercurio, afectando el crecimiento de la biomasa leñosa. La recuperación significativa en las zonas de sobrecarga indica que una posible estrategia de remediación activa para promover la recuperación de biomasa puede ser rellenar pozos y estanques mineros con tierra excavada. Resumo: Nos últimos anos, a mineração de ouro aumentou rapidamente em toda a Bacia Amazônica, especialmente no escudo da Guiana, onde é responsável por >90% do desmatamento total. No entanto, a capacidade das florestas de se recuperar das atividades de mineração permanece praticamente não quantificada. Para obter a primeira quantificação dos impactos da mineração de ouro na recuperação de biomassa da floresta amazônica, parcelas florestais foram instaladas em minas recentemente abandonadas em duas grandes regiões de mineração na Guiana e remedidas após 18 meses. Nossos resultados evidenciam que as taxas de recuperação de biomassa lenhosa em poços de mineração abandonados e lagoas de rejeitos, estão entre as mais baixas já registradas para florestas tropicais: quase nenhuma recuperação de biomassa lenhosa após 3–4 anos. Nos locais de sobrecarga (áreas não mineradas, mas onde o solo escavado é depositado), as taxas de recuperação de biomassa acima do solo (0, 4–5, 4 Mg ha −1  ano −1 ) estavam dentro do registrado em outras florestas secundárias nos Neotrópicos, após o abandono de pastagens e terras agrícolas. Nossos resultados sugerem que a recuperação da floresta é mais fortemente limitada pela severa redução dos nutrientes do solo, induzida pela mineração. A recuperação é particularmente mais limitada pelos baixos teores de nitrogênio, do que pela contaminação por mercúrio, devido à redução do crescimento em solos desprovidos de nutrientes. Estimamos que as baixas taxas de recuperação em poços e lagoas de mineração atualmente reduzam o sequestro de carbono nas florestas secundárias da Amazônia em aproximadamente 21.000 t C/ano, em relação ao carbono potencialmente acumularia após usos mais tradicionais como agricultura ou pastagem. Síntese e aplicações . Para alcançar metas de restauração em larga escala, a Guiana e outros países da Amazônia serão desafiados a remediar as terras mineradas anteriormente. O processo de recuperação da biomassa lenhosa é altamente dependente da disponibilidade de nitrogênio, e não da contaminação por mercúrio. A maior recuperação em zonas de sobrecarga indica que uma estratégia potencial de remediação ativa para promover a recuperação de biomassa, consiste potencialmente no preenchimento de poços e lagoas de mineração com solo escavado.